THE ROLE OF PEOPLE’S ORAL CREATION IN THE EDUCATIONAL PROCESS - Egamberdiyeva Yulduz Urinboyevna; Mirzokhayitova Muazzam Umidjon qizi (Web of Journals Publishing, 2024)
This article discusses the role of folklore in the process of education, the importance of folklore in education, its content and effects.
Keywords: reform, education - training, future, young generation, mature generation, samples of folk oral creativity, integration (relationship).